Effect of pre-treatment on physical properties, ascorbic acid and -carotene content of frozen sweet corn kernels hibrimas (Zea mays var Saccharata bailey) variety - Zamzahaila Mohd Zin,; Phang, Yan Man; Nasution, Zuraidah; Chong, Kah Hui; Mohamad Khairi Zainol, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The main objective of this study is to investigate the best pre-treatment based on physical properties, ascorbic acid and β-carotene content of frozen sweet corn kernels of the Hibrimas variety. Five types of pre-treatments being studied: water blanching, steam blanching, 0.5% citric acid blanching, 2.0% sodium chloride blanching and 1.0% sodium metabisulfite blanching. It was discovered that sodium metabisulfite blanching can improve texture of frozen corn kernels while citric acid blanching play vital role in colour and total soluble solids retention. pH value is more stable after subjected to steam pretreatment. Chemical pre-treatments were outweighing physical pre-treatments in ascorbic acid retention. There were no significant effects showed by pre-treatments on storage weight loss and β-carotene content. Citric acid pre-treatment was suggested to be the best pre-treatment due to its high colour and total soluble content.